Integrasi Islamic, Science, Technology, Engineering, Art, and Math (ISTEAM) dalam Pembelajaran (Studi Kasus di UIN Ar-Raniry) - Nuraida; Sofyan Arianto; Nurasiah; Cut Intan Hayati (Jurnal Kolaborasi Akademika, 2026)
The integration of interdisciplinary education that combines spiritual values with scientific competence has become an urgent necessity in the Society 5.0 era. This study aims to analyze the implementation of the ISTEAM (Islamic, Science, Technology, Engineering, Art, and Mathematics) learning model at the State Islamic University (UIN) Ar-Raniry Banda Aceh. Using a qualitative case study approach, data were collected through classroom observations, curriculum document reviews, and in-depth interviews with the academic community. The findings indicate that UIN Ar-Raniry has adopted the Wahdatul Ulum paradigm, which integrates kauniyyah and qur'aniyyah verses into courses such as Fundamentals of Islamic Science. The implementation of ISTEAM is proven to enhance students' critical thinking, creativity, and technological literacy while strengthening religious character. However, challenges such as limited integrative teaching materials and the need for increased lecturer capacity in interdisciplinary design remain major obstacles. Strengthening strategies through cross-faculty collaboration and the development of project-based modules are highly recommended for future curriculum optimization.